Sermon on the mount: a beginner's guide to the kingdom of heaven - Levine, Amy-Jill (Abingdon Press, 2020)
"What must it have been like to hear Jesus deliver the Sermon on the Mount? What did his words mean to people in the crowd and how did it change their lives? Did his listeners interpret the sermon as we do now? In this 6-week study based on Matthew 5-7, Dr. Amy-Jill Levine explores the major topics in the most popular sermon ever delivered, using a solid knowledge of Hebrew Scriptures and moral teachings. Additional components include a DVD featuring Dr. Levine and a comprehensive Leader Guide. Toward the Kingdom of Heaven, a collection of 40 daily devotionals, is also included"--